Innovative Activities in the Sphere of Mining Process Management - Bazaluk, Oleg; Ashcheulova, Oleksandra; Mamaikin, Oleksandr; Khorolskyi, Andrii; Lozynskyi, Vasyl; Saik, Pavlo (Frontiers in Environmental Science, 2022)
The purpose of this paper is to propose a new methodological approach to complex assessment of coal-mining enterprises basing on the evaluation of technological schemes from the viewpoint of their susceptibility to innovations. To solve the specified problems, a complex method has been used. The method involves geometrical interpretation of a task of determining boundary parameters of technological schemes, application of criteria-based estimations for determining a level of production efficiency, and use of complex index of economic re liability. For the first time, optimality criteria for innovation management in coal industry have been proposed; they take into consideration a level of organization of innovations, organization of innovative production system, and organization of innovative production process. A complex index “internal potential of technological networks” has been developed, being one of the essential parameters for evaluating coal mine conditions. It has been identified that its formation is the result of the influence of certain factors determining the underground mining efficiency and, first of all, the coal mine property – spatial development. According to the represented concept, a policy of optimal control for maintaining the operating mine capacities is based on the evaluation of remained reserves, substantiated planning of a stoping line, and correspondence of extraction equipment to the operating conditions. It is possible to increase the concentration of production by redistributing the remained reserves and integration of mines by mining operations; that makes it possible to concentrate resources within those parts of a mine field where the effect will show its maximum. Modelling of such problems is based on a system of constraints without any requirements for providing the planned mine loading, obligatory in the past. Analysis of the indices of efficiency of coal-mining technological schemes and accounting of the developed factual system of indices have helped elaborate recommendations concerning the use of optimality criteria in the organizational tasks of assessment of the potential of technological scheme of mines. Further application of graphs and network models will allow optimizing the mining production parameters. Consequently, the carried out research has resulted in a new system as for innovation management in a mining complex.